The International Association for the Study of Lung Cancer Consensus Statement on Optimizing Management ofEGFRMutation–Positive Non–Small Cell Lung Cancer: Status in 2016. Issue 7 (July 2016) - Tan, Daniel S.W.; Yom, Sue S.; Tsao, Ming S.; Pass, Harvey I.; Kelly, Karen; Peled, Nir; Yung, Rex C.; Wistuba, Ignacio I.; Yatabe, Yasushi; Unger, Michael; Mack, Philip C.; Wynes, Murry W.; et al.
ABSTRACT : N/A: Mutations in the epidermal growth factor receptor gene ( EGFR ) represent one of the most frequent "actionable" alterations in non–small cell lung cancer (NSCLC). Typified by high response rates to targeted therapies, EGFR tyrosine kinase inhibitors (TKIs) are now established first‐line treatment options and have transformed the treatment paradigm for NSCLC. With the recent breakthrough designation and approval of the third‐generation EGFR TKI osimertinib, available systemic and local treatment options have expanded, requiring new clinical algorithms that take into account individual patient molecular and clinical profiles. In this International Association for the Study of Lung Cancer commissioned consensus statement, key pathologic, diagnostic, and therapeutic considerations, such as optimal choice of EGFR TKI and management of brain metastasis, are discussed. In addition, recommendations are made for clinical guidelines and research priorities, such as the role of repeat biopsies and use of circulating free DNA for molecular studies. With the rapid pace of progress in treating EGFR ‐mutant NSCLC, this statement provides a state‐of‐the‐art review of the contemporary issues in managing this unique subgroup of patients.